Dilemma of Traditional Market Traders in the Era of Digital Transformation: Case Study at Wlingi Blitar Market - Edi Murdiyanto; Sudarmiatin Sudarmiatin (JURNAL EKONOMI BISNIS DAN MANAJEMEN, 2024)
Traditional traders, especially clothing traders, have experienced a decline in sales amidst the development of modern markets and online sales. The research raised a case study in the Wlingi Blitar market, the largest market in the Blitar district, East Java. Research using a qualitative approach is presented descriptively, resources are obtained through in-depth interviews and also documenting, making observations, and using secondary data to obtain in-depth information so that a complete picture is obtained regarding the topic of traditional markets, modern markets, and digital transformation which has given rise to online sales. The research results stated that clothing traders experienced a decline in sales caused by the emergence of many modern shops in the Wlingi area and its surroundings and due to the rise of online sales. Some market sellers can transform sales digitally by selling their products online, but some traders need help to do this, so sales experience a decline.